Corrigendum to ’In-situ Elastic Calibration of Robots: Minimally-Invasive Technology, Cover-Based Pose Search and Aerospace Case Studies’, Robotics and Computer-Integrated Manufacturing 89 (2024), 102743 - Monsarrat, Bruno; Audet, Julien-Mathieu; Fortin, Yves; Côté, Gabriel; Vistein, Michael; Brandt, Lars; Sadek, Ahmad; Krebs, Florian (Robotics and computer-integrated manufacturing, 2024)
The authors provide a corrigendum for two equations of their published article [1]. These corrections do not impact the general kinetostatic model, elastic calibration algorithms, case studies’ results and conclusions presented in the article.